Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0138590
|View full text |Cite
|
Sign up to set email alerts
|

The Green Tea Component (-)-Epigallocatechin-3-Gallate Sensitizes Primary Endothelial Cells to Arsenite-Induced Apoptosis by Decreasing c-Jun N-Terminal Kinase-Mediated Catalase Activity

Abstract: The green tea component (-)-epigallocatechin-3-gallate (EGCG) has been shown to sensitize many different types of cancer cells to anticancer drug-induced apoptosis, although it protects against non-cancerous primary cells against toxicity from certain conditions such as exposure to arsenic (As) or ultraviolet irradiation. Here, we found that EGCG promotes As-induced toxicity of primary-cultured bovine aortic endothelial cells (BAEC) at doses in which treatment with each chemical alone had no such effect. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Pretreatment with EGCG doseā€dependently reduced IRā€induced expression of survivin leading to significantly increased radiosensitivity and decreased cell proliferation . However, EGCG made bortezomib less effective by an autophagy mechanism and promoted arseniteā€induced toxicity in primaryā€cultured bovine aortic endothelial cells, suggesting that green tea products should be contraindicated during bortezomib or arsenite therapy . Furthermore, the doses of the combination of EGCG and anticancer drugs have been shown in Table , which demonstrated that EGCG at low doses (about 5 Ī¼M) might have the chemoprotective effect combining with anticancer agents (such as doxorubicin).…”
Section: Combinational Effects Of Egcg and Other Anticancer Agentsmentioning
confidence: 99%
“…Pretreatment with EGCG doseā€dependently reduced IRā€induced expression of survivin leading to significantly increased radiosensitivity and decreased cell proliferation . However, EGCG made bortezomib less effective by an autophagy mechanism and promoted arseniteā€induced toxicity in primaryā€cultured bovine aortic endothelial cells, suggesting that green tea products should be contraindicated during bortezomib or arsenite therapy . Furthermore, the doses of the combination of EGCG and anticancer drugs have been shown in Table , which demonstrated that EGCG at low doses (about 5 Ī¼M) might have the chemoprotective effect combining with anticancer agents (such as doxorubicin).…”
Section: Combinational Effects Of Egcg and Other Anticancer Agentsmentioning
confidence: 99%
“…Arsenic, a recognized cardiovascular toxicant, has exhibited mito-toxic effects in vascular smooth muscle [ 44 ], myocardial cells [ 45 ], and vascular endothelial cells [ 46 ]. Arsenic is associated with mitochondrial dysfunction through mechanisms such as elevated ROS, induction of apoptosis, and Ca 2+ overload.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG is a major component of polyphenols in green tea [ 14 , 15 ]. It has inhibitory effects on cell transformation and early cancerization, ROS generation and DNA damage induced by inflammation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%